Business Cycle Transmission from the US to Germany: a Structural Factor Approach - Sandra Eickmeier (Deutsche Bundesbank, 2004)
This paper investigates the transmission of US macroeconomic shocks to Germany by employing a large-dimensional structural dynamic factor model. This framework allows us to investigate many transmission channels simultaneously, including 'new' channels like stock markets, foreign direct investment, bank lending and the confidence channel. We find that US shocks affect the US and Germany largely symmetrically. Trade and monetary policy reactions to strong price effects seem to be most relevant; financial markets may have become more important over time. The speed of transmission does not seem to have increased. Negative domestic influences apparently more than compensated positive US influences in the German economy between 1995 and 2000, but the US recession in 2001 seemed mainly responsible for the German slump.
Keywords: F41; C13; C32; F02; 330; International business cycles; international transmission channels; dynamic factor models; structural VAR techniques; Konjunkturzusammenhang; VAR-Modell; Schätzung; Vereinigte Staaten; Deutschland